2010
DOI: 10.1111/j.1365-2745.2010.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of biological collections as a source of phenological data for use in climate change studies: a case study with the orchid Ophrys sphegodes

Abstract: Summary1. The scarcity of reliable long-term phenological data has severely hindered the study of the responses of species to climate change. Biological collections in herbaria and museums are potential sources of long-term data for such study, but their use for this purpose needs independent validation. Here we report a rigorous test of the validity of using herbarium specimens for phenological studies, by comparing relationships between climate and time of peak flowering derived from herbarium records and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
176
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 29 publications
6
176
0
4
Order By: Relevance
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
supporting
confidence: 79%
“…In addition, our analysis of specimens for which at least month of collection was available yielded similar results to those for which day of collection was available. This suggests that even "incomplete" data such as these, which are often discarded from analysis (11,54,56), may merit examination.Finally, a decline in botanical collection in recent years noted by other authors (10, 54) is also reflected in our data (Fig. S1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Los hábitats de plantas silvestres, como las orquídeas, han sido afectadas negativamente por la interferencia humana y el cambio climático (Robbirt, Davy, Hutchings, & Roberts, 2011;Sánchez, Osborne, & Haq, 2011). Para evaluar estos efectos, los modelos de distribución de especies son una herramienta útil (Guisan & Zimmermann, 2000;De Marco Junior & Siqueira, 2009;Siqueira & Durigan, 2007), ya que permiten identificar áreas potenciales donde puede desarrollarse la especie, y predecir cambios en las zonas de distribución (Rezende, Oliveira-Filho, Eisenlohr, Kamino, & Vibrans, 2014).…”
unclassified